A proposed Global Boundary Stratotype Section and Point for the base of the Middle Ordovician Series: The Niquivil section, Precordillera of San Juan, Argentina - Albanesi, Guillermo Luis (2006)
The Niquivil section, Argentine Precordillera, fulfills most of the requirements for a Global Stratotype Section and Point (GSSP) for the base of the Middle Ordovician Series. It has excellent conodont biostratigraphy in a continuous succession of uniform lithology, is readily accessible, and the critical interval is not tectonically affected. The position of the Lower/Middle Ordovician Series boundary in the Central Precordillera is placed at the middle part of the San Juan Formation, an open-platform carbonate unit. The Niquivil section is proposed as a GSSP for the base of the Middle Ordovician, which is marked by the FAD of the conodont Cooperignathus aranda (Cooper). It occurs in level NCA, at the upper part of the Oepikodus evae Zone (overlapping uppermost records of O. evae in association with other guide species); i.e., 100.15 m above the base of the reference section. The auxiliary Peña Sombría section from northern Precordillera records graptolites of the lower (but not lowest) Middle Ordovician in the Isograptus victoriae maximus Zone, few meters above the proposed boundary biohorizon. The range of C. aranda can be correlated with the I. victoriae lunatus Zone up to the lower part of the Undulograptus austrodentatus Zone in diverse sections of the world. C. aranda presents cosmopolitan distribution and occurs in virtually all environments. The proposed GSSP preserves a carbon-isotope record that provides an auxiliary marker of potential global application. Radiometric dating of K-bentonite samples, interbedded with carbonate strata yielding lower records of C. aranda, were recovered from the auxiliary Talacasto section in Central Precordillera (469.8 ± 2.3 Ma, U–Pb SHRIMP dating).Cooperignathus aranda (Cooper). It occurs in level NCA, at the upper part of the Oepikodus evae Zone (overlapping uppermost records of O. evae in association with other guide species); i.e., 100.15 m above the base of the reference section. The auxiliary Peña Sombría section from northern Precordillera records graptolites of the lower (but not lowest) Middle Ordovician in the Isograptus victoriae maximus Zone, few meters above the proposed boundary biohorizon. The range of C. aranda can be correlated with the I. victoriae lunatus Zone up to the lower part of the Undulograptus austrodentatus Zone in diverse sections of the world. C. aranda presents cosmopolitan distribution and occurs in virtually all environments. The proposed GSSP preserves a carbon-isotope record that provides an auxiliary marker of potential global application. Radiometric dating of K-bentonite samples, interbedded with carbonate strata yielding lower records of C. aranda, were recovered from the auxiliary Talacasto section in Central Precordillera (469.8 ± 2.3 Ma, U–Pb SHRIMP dating).(Cooper). It occurs in level NCA, at the upper part of the Oepikodus evae Zone (overlapping uppermost records of O. evae in association with other guide species); i.e., 100.15 m above the base of the reference section. The auxiliary Peña Sombría section from northern Precordillera records graptolites of the lower (but not lowest) Middle Ordovician in the Isograptus victoriae maximus Zone, few meters above the proposed boundary biohorizon. The range of C. aranda can be correlated with the I. victoriae lunatus Zone up to the lower part of the Undulograptus austrodentatus Zone in diverse sections of the world. C. aranda presents cosmopolitan distribution and occurs in virtually all environments. The proposed GSSP preserves a carbon-isotope record that provides an auxiliary marker of potential global application. Radiometric dating of K-bentonite samples, interbedded with carbonate strata yielding lower records of C. aranda, were recovered from the auxiliary Talacasto section in Central Precordillera (469.8 ± 2.3 Ma, U–Pb SHRIMP dating).Oepikodus evae Zone (overlapping uppermost records of O. evae in association with other guide species); i.e., 100.15 m above the base of the reference section. The auxiliary Peña Sombría section from northern Precordillera records graptolites of the lower (but not lowest) Middle Ordovician in the Isograptus victoriae maximus Zone, few meters above the proposed boundary biohorizon. The range of C. aranda can be correlated with the I. victoriae lunatus Zone up to the lower part of the Undulograptus austrodentatus Zone in diverse sections of the world. C. aranda presents cosmopolitan distribution and occurs in virtually all environments. The proposed GSSP preserves a carbon-isotope record that provides an auxiliary marker of potential global application. Radiometric dating of K-bentonite samples, interbedded with carbonate strata yielding lower records of C. aranda, were recovered from the auxiliary Talacasto section in Central Precordillera (469.8 ± 2.3 Ma, U–Pb SHRIMP dating).O. evae in association with other guide species); i.e., 100.15 m above the base of the reference section. The auxiliary Peña Sombría section from northern Precordillera records graptolites of the lower (but not lowest) Middle Ordovician in the Isograptus victoriae maximus Zone, few meters above the proposed boundary biohorizon. The range of C. aranda can be correlated with the I. victoriae lunatus Zone up to the lower part of the Undulograptus austrodentatus Zone in diverse sections of the world. C. aranda presents cosmopolitan distribution and occurs in virtually all environments. The proposed GSSP preserves a carbon-isotope record that provides an auxiliary marker of potential global application. Radiometric dating of K-bentonite samples, interbedded with carbonate strata yielding lower records of C. aranda, were recovered from the auxiliary Talacasto section in Central Precordillera (469.8 ± 2.3 Ma, U–Pb SHRIMP dating).Isograptus victoriae maximus Zone, few meters above the proposed boundary biohorizon. The range of C. aranda can be correlated with the I. victoriae lunatus Zone up to the lower part of the Undulograptus austrodentatus Zone in diverse sections of the world. C. aranda presents cosmopolitan distribution and occurs in virtually all environments. The proposed GSSP preserves a carbon-isotope record that provides an auxiliary marker of potential global application. Radiometric dating of K-bentonite samples, interbedded with carbonate strata yielding lower records of C. aranda, were recovered from the auxiliary Talacasto section in Central Precordillera (469.8 ± 2.3 Ma, U–Pb SHRIMP dating).Zone, few meters above the proposed boundary biohorizon. The range of C. aranda can be correlated with the I. victoriae lunatus Zone up to the lower part of the Undulograptus austrodentatus Zone in diverse sections of the world. C. aranda presents cosmopolitan distribution and occurs in virtually all environments. The proposed GSSP preserves a carbon-isotope record that provides an auxiliary marker of potential global application. Radiometric dating of K-bentonite samples, interbedded with carbonate strata yielding lower records of C. aranda, were recovered from the auxiliary Talacasto section in Central Precordillera (469.8 ± 2.3 Ma, U–Pb SHRIMP dating).C. aranda can be correlated with the I. victoriae lunatus Zone up to the lower part of the Undulograptus austrodentatus Zone in diverse sections of the world. C. aranda presents cosmopolitan distribution and occurs in virtually all environments. The proposed GSSP preserves a carbon-isotope record that provides an auxiliary marker of potential global application. Radiometric dating of K-bentonite samples, interbedded with carbonate strata yielding lower records of C. aranda, were recovered from the auxiliary Talacasto section in Central Precordillera (469.8 ± 2.3 Ma, U–Pb SHRIMP dating).I. victoriae lunatus Zone up to the lower part of the Undulograptus austrodentatus Zone in diverse sections of the world. C. aranda presents cosmopolitan distribution and occurs in virtually all environments. The proposed GSSP preserves a carbon-isotope record that provides an auxiliary marker of potential global application. Radiometric dating of K-bentonite samples, interbedded with carbonate strata yielding lower records of C. aranda, were recovered from the auxiliary Talacasto section in Central Precordillera (469.8 ± 2.3 Ma, U–Pb SHRIMP dating).Undulograptus austrodentatus Zone in diverse sections of the world. C. aranda presents cosmopolitan distribution and occurs in virtually all environments. The proposed GSSP preserves a carbon-isotope record that provides an auxiliary marker of potential global application. Radiometric dating of K-bentonite samples, interbedded with carbonate strata yielding lower records of C. aranda, were recovered from the auxiliary Talacasto section in Central Precordillera (469.8 ± 2.3 Ma, U–Pb SHRIMP dating).C. aranda presents cosmopolitan distribution and occurs in virtually all environments. The proposed GSSP preserves a carbon-isotope record that provides an auxiliary marker of potential global application. Radiometric dating of K-bentonite samples, interbedded with carbonate strata yielding lower records of C. aranda, were recovered from the auxiliary Talacasto section in Central Precordillera (469.8 ± 2.3 Ma, U–Pb SHRIMP dating).C. aranda, were recovered from the auxiliary Talacasto section in Central Precordillera (469.8 ± 2.3 Ma, U–Pb SHRIMP dating).